Mandatory tuberculosis case notification in high tuberculosis-incidence countries: policy and practice. Issue 6 (20th October 2016) - Uplekar, Mukund; Atre, Sachin; Wells, William A.; Weil, Diana; Lopez, Rafael; Migliori, Giovanni Battista; Raviglione, Mario
Mandatory tuberculosis (TB) notification is an important policy under the End TB Strategy, but little is known about its enforcement especially in high TB incidence countries. We undertook a literature search for selected high-incidence countries, followed by a questionnaire-based survey among key informants in countries with high-, intermediate- and low-TB incidence. Published literature on TB notification in high-incidence countries was limited, but it did illustrate some of the current barriers to notification and the importance of electronic systems to facilitate reporting by private providers. Required survey data were successfully gathered from 40 out of 54 countries contacted. TB is notifiable in 11 out of 15 high-incidence countries, all 16 intermediate-incidence countries, and all nine low-incidence countries contacted. TB case notification by public sector facilities is generally systematised, but few high-incidence countries had systems and tools to facilitate notification from private care providers. In the context of the new End TB Strategy aimed at eventual TB elimination, all countries should have TB on their national list of notifiable diseases. Enhancing the ease of notification by private providers is essential for effective implementation. To that effect, investing in strengthening disease surveillance systems and introducing digital tools to simplify notification are logical ways forward. Mandatory case notification weak in high TB-burden countries; requires simple tools for private providers http://ow.ly/wZ9Z303bidB